2021
DOI: 10.1177/0095399721997427
|View full text |Cite
|
Sign up to set email alerts
|

How Do Leaders Influence Innovation and Creativity in Employees? The Mediating Role of Intrinsic Motivation

Abstract: Drawing on the social exchange theory, this research examines how inclusive leaders foster innovative work behavior and creativity in employees. Data were collected in two steps from the 320 employees working in Chinese R&D organizations to draw the result for this research. The findings indicate a positive impact of inclusive leadership on innovative work behavior and creativity. In addition, intrinsic motivation mediates this relationship. The implications and future research are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 81 publications
1
56
0
5
Order By: Relevance
“…According to prior study, the presence of leadership has a considerable impact on participation in creativity-relevant procedures or processes because leaders play an important role in creating a creative environment inside the organization (Reiter-Palmon and Illies, 2004;Siyal et al, 2021). Previous research has shown that servant leadership has a good influence on staff creativity.…”
Section: Discussionmentioning
confidence: 99%
“…According to prior study, the presence of leadership has a considerable impact on participation in creativity-relevant procedures or processes because leaders play an important role in creating a creative environment inside the organization (Reiter-Palmon and Illies, 2004;Siyal et al, 2021). Previous research has shown that servant leadership has a good influence on staff creativity.…”
Section: Discussionmentioning
confidence: 99%
“…This paper's aim was to investigate the moderating effect of green brand knowledge (GBK) on the relationship of green brand positioning (GBP), attitude towards green brand (ATGB), environmental concern (EC) and green purchase intention (GPI). Therefore, this study is explanatory in nature and uses PLS SEM [114,115] following [116,117]. In other words, Sekaran and Bougie [118] further shared two types of studies, cross-sectional and longitudinal.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, customers with global reach have removed the slightest semblance of being local (Lenka and Gupta, 2019). Ensuing heightened competition compels firms to be attentive toward their pursuit of innovation, given that it is one of the ways to ensure survival and growth in the intensifying competition (Anning-Dorson and Nyamekye, 2020; Siyal et al, 2021). Previously, relative stability allowed leaders to gather knowledge to guide their firms toward new ideas, but this enticing stability has disappeared.…”
Section: Innovation With Flow At Work 1267mentioning
confidence: 99%